Sytuacja ekonomiczno-finansowa i prawna prywatnych majątków ziemskich w Polsce w okresie międzywojennym - Zając, Stanisław (Leśne Prace Badawcze, 2013)
The bad economic situation for agro-forest farms in Poland during the interwar period was caused by war damage, a global economic crisis, crop failure, indebtedness prior to World War I, and by tribute payments towards rebuilding the country. Although the timber harvest was substantial, farm owners were forced to take out loans. In 1938, the debt level of agro-forest farms accounted for 18 per cent of their total value. The average debt level for this period oscillated between 9.8 and 126.0 PLN ha-1. The assistance programme implemented by the government provided for a reduction in the interest rate of loans, particularly for farms with an area of up to 300 ha.